PERANAN ZAINAL ABIDIN PAGARALAM BIDANG POLITIK DAN SOSIAL TERHADAP PERKEMBANGAN PROVINSI LAMPUNG TAHUN 1966-1972 - Sendy Prabowo; Sumiyatun Sumiyatun (Swarnadwipa, 2018)
The condition of Lampung Province as a new province still requires a lot of improvement in various fields, both in the field of politics and social field, it is caused in the period of leadership of First Governor Kusno Danupojo, Lampung as the new Province, only focused on the transfer of status of Lampung as Residency of Sumatra South became Independent Province on March 18, 1964. So the development needs to be contineu by Zainal Abidin Pagaralam as the second governor who served 1966-1972. The problem in this research is in developing the Province of Lampung in the field of Political and Social Zainal Abidin Pagaralam experience many obstacles and challenges This research is a historical research, conducted in the Library University Muhammadiyah MetroData collection techniques in this study using heuristic steps and literature techniques and the validity of data collection using internal and external criticism with the steps of analysis that is using the step of interpretation and historiography. Conclusion of historical conclusion: 1.  In the field of politics conducted by Zainal Abidin Pagaralam is to improve governance and employee bureaucracy in Lampung Provincial Government by instilling discipline soul and moral values. 2 In the social field of Zainal Abidin Pagaralam by building public facilities of public needs, namely road, schools University, Banking, and rehabilitate the Hospital of Abdoel Moelok and build a new governor office